Ethnobotanical survey and therapeutic potentials of medicinal Fabaceae in Katsina State, Nigeria - Tukur, Khalid; Besi, Edward Entalai; Nulit, Rosimah; Kankara, Sulaiman Sani; Go, Rusea (Springer Nature, 2026)
Fabaceae plays a crucial role in traditional medicine, ecology, and nutrition. This study aims to provide an extensive ethnomedicinal checklist of Fabaceae plants used in Katsina State, Nigeria, where such ethnobotanical documentation has not yet been conducted. We compiled data on the traditional uses of Fabaceae species to treat ailments through semi-structured questionnaires administered to 180 respondents across nine local government areas. Respondents included herbalists, farmers, traders, civil servants, and others. We employed Relative Frequency of Citation, Fidelity Level, and the Informant Consensus Factor to analyze usage trends and cultural consensus. The findings revealed a total of 81 species belonging to 45 genera, with Indigofera and Crotalaria being the most represented at 15% each. These plants are traditionally used to treat gastrointestinal disorders, fever, and piles, as well as to enhance overall well-being. This study underscores the importance of conserving this rich traditional knowledge and highlights the need for further research on the most frequently mentioned species regarding their pharmacological potential. Validating these plants could provide new options for modern medicine while helping to preserve biodiversity and cultural heritage.